2018
DOI: 10.1371/journal.pone.0206553
|View full text |Cite
|
Sign up to set email alerts
|

Under expression of the Sonic Hedgehog receptor, Patched1 (PTCH1), is associated with an increased risk of local recurrence in squamous cell carcinoma of the vulva arising on a background of Lichen Sclerosus

Abstract: ObjectiveDysregulation of the Hedgehog (Hh) pathway has been described in a variety of cancers, including cervical cancer, a disease which shares a common aetiology with vulval squamous cell carcinoma (VSCC). Here, we investigate a large number of primary VSCC cases for evidence of Hedgehog pathway activation and examine the implications of pathway activity on clinical outcomes in a cohort of patients with primary VSCC.MethodsArchival histology blocks containing VSCC and histologically normal adjacent epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In relation to previous reports [7,32], which revealed significant positive correlation between SHH overexpression and lymphatic metastasis of patients with OSCC, our study showed slight trend toward higher SHH expression in OSCC with lymph node metastasis. Similarly, to Yap et al [13], who pointed the clinical benefit from SHH overexpression in patients with squamous cell carcinoma of the vulva (VSCC), we might suggest that high SHH expression in OSCC tissue can be used as a biomarker to stratify patients of the risk of lymph node metastasis. SHH protein was an independent prognostic biomarker for poor prognosis in patients with OSCC.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In relation to previous reports [7,32], which revealed significant positive correlation between SHH overexpression and lymphatic metastasis of patients with OSCC, our study showed slight trend toward higher SHH expression in OSCC with lymph node metastasis. Similarly, to Yap et al [13], who pointed the clinical benefit from SHH overexpression in patients with squamous cell carcinoma of the vulva (VSCC), we might suggest that high SHH expression in OSCC tissue can be used as a biomarker to stratify patients of the risk of lymph node metastasis. SHH protein was an independent prognostic biomarker for poor prognosis in patients with OSCC.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, we estimated SHH, p53, HPV expression and association between these proteins in OSCC tissue in order to establish their impact on tumor progression as well to define its prognostic significance in patients with OSCC. The majority of published data claims that uncontrolled upregulation of the Sonic hedgehog signaling pathway results in carcinogenesis and tumor growth [9,13,26]. Upregulation of SHH was described in some solid tumors (e.g., breast, esophageal, lung cancer) suggesting that SHH may be responsible for highly invasive biological behavior of tumor, but it is still little known about its role in OSCC [29,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was proven in that study that the overexpression of Kif7 in the choriocarcinoma cell lines, JAR and JEG-3, suppressed cell migration, the role of SHH in the development of gestational trophoblastic neoplasms remains unclear ( 160 ). Furthermore, only one study focused on SHH expression in vulvar squamous cell carcinoma (VSCC); Yap et al ( 161 ) performed semi-quantitative IHC of tissue specimens from 91 VSCC cases for SHH, PTCH1 and GLI1 proteins. Although an increased immunoreactivity of one or more of the assessed proteins was reported, only the decreased expression of PTCH1 was associated with an increased risk of developing a local disease recurrence ( 161 ).…”
Section: Shh Pathway In Gynecological Cancersmentioning
confidence: 99%
“…Furthermore, only one study focused on SHH expression in vulvar squamous cell carcinoma (VSCC); Yap et al ( 161 ) performed semi-quantitative IHC of tissue specimens from 91 VSCC cases for SHH, PTCH1 and GLI1 proteins. Although an increased immunoreactivity of one or more of the assessed proteins was reported, only the decreased expression of PTCH1 was associated with an increased risk of developing a local disease recurrence ( 161 ).…”
Section: Shh Pathway In Gynecological Cancersmentioning
confidence: 99%